PERAN KEPEMIMPINAN, LINGKUNGAN KERJA DAN KECERDASAN EMOSIONAL TERHADAP PRODUKTIVITAS KERJA DI PERUSAHAAN MANUFAKTUR - Iwan Irwanto; Tirta Agri Dharma Ramaulana; Ade Solahudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The era of rapid transformation has increased business competition, making high work productivity critical to organizational success. However, Indonesia has experienced a decline in productivity due to factors such as delays in technological advances and an inflexible labor market. This study aims to examine the role of leadership, work environment, and emotional intelligence on work productivity at PT Siradj Badawi Cukup Rupiah (SBCR), a sauce industry and consumer goods distribution company in Cirebon. A quantitative approach was used with a survey method, where data were collected through questionnaires from 100 production employees. Data were analyzed using SPSS 25 with multiple linear regression. The results showed that leadership, work environment, and emotional intelligence each had a positive and significant effect on work productivity. In addition, these three factors jointly influence work productivity, confirming the importance of strong leadership, a conducive work environment, and employees' emotional intelligence in improving efficiency and achieving company goals. These findings provide valuable insights for companies seeking to optimize workforce performance and organizational success.